2012
DOI: 10.1097/jcp.0b013e3182664dbc
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for More Than 3 Years’ Duration of Central Stimulant Treatment in Adult Attention-Deficit/Hyperactivity Disorder

Abstract: There is effective short-term central stimulant (CS) treatment of attention-deficit/hyperactivity disorder (ADHD) symptoms in adult ADHD, and despite this, many patients discontinue the treatment too early. The present study examines the duration of CS treatment in a Norwegian cohort of adult ADHD to identify predictors for long treatment duration (≥ 3 years). The data were based on the medical records of a sample of 117 of all 119 adult ADHD patients diagnosed over a period of 8 years in a specific catchment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
10
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 29 publications
6
10
1
Order By: Relevance
“…Retrospective studies have found comorbidity related to less adherence to medication (Lensing et al, 2013;Torgersen et al, 2012), corresponding with our findings of less comorbidity among those adherent to treatment.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Retrospective studies have found comorbidity related to less adherence to medication (Lensing et al, 2013;Torgersen et al, 2012), corresponding with our findings of less comorbidity among those adherent to treatment.…”
Section: Discussionsupporting
confidence: 89%
“…However, we found no gender differences in the global GAF-measures or for mental distress, and adherence at endpoint did not differ between the sexes, similar to reports by a 3 years retrospective study (Torgersen et al, 2012). Improvement on medication was found despite presence of comorbid psychiatric disorders.…”
Section: Discussionsupporting
confidence: 88%
“…Cmorbid anxiety and bipolar disorders were associated with less effectiveness adjusted for age, gender and dosage. Retrospective studies have found comorbidity related to less adherence to medication , and this corresponds with our findings with less comorbidity among those adherent to treatment. Medication dosages were in line with other medication studies in adults with ADHD .…”
Section: Discussionsupporting
confidence: 92%
“…Adler and Nierenberg (2010) noted that attrition approaches 65% in long-term ADHD studies, but did not address the reasons this occurs. Torgersen et al (2012) reported that adults with ADHD and antisocial personality had elevated dropout rates, whereas Lensing et al (2013) felt that treatment noncompliance in ADHD adults is associated with comorbidity. Victor et al (2009) found as well that comorbidity was associated with attrition.…”
mentioning
confidence: 97%